PERANAN GURU AGAMA HINDU DALAM MENINGKATKAN KARAKTER DISIPLIN SISWA KELAS V DI SDN 11 CAKRANEGARA - Utami, Ni Luh Eka Savitri; Putera, Gusti Ngurah Ketut; Rudiarta, I Wayan (Padma Sari: Jurnal Ilmu Pendidikan, 2024)
Disciplinary character is important in the world of education. The problem of disciplinary character that occurs at Elementary School 11 Cakranegara is some students play during tri sandhya activities, pay less attention to the teacher's explanation, and are also indifferent to the tasks given by the teacher. This study aims to provide information about the role of Hindu Religious Teachers in improving students' disciplinary character. The problems studied are The disciplinary character of 5th-grade students at Elementary School 11 Cakranegara; The role of Hinduism teachers in improving the disciplinary character of 5th-grade students; Efforts made by Hinduism teachers in improving the disciplinary character of 5th-grade students at Elementary School 11 Cakranegara. This research uses a descriptive qualitative approach method. Through observation, interview, and documentation data collection techniques. The results showed: 1. The disciplinary character of 5th-grade students is good enough. It is proven that they have fulfilled the existing discipline character indicators. 2. The role of Hinduism teachers in improving the disciplinary character of 5th-grade students is vital. The role consists of Teachers as educators and teachers, facilitators, motivators, and demonstrators. 3. Efforts made by Hinduism teachers in improving the disciplinary character of 5th-grade students: Reprimanding students, guiding students, making picket schedules in groups, providing coaching and direction to students, making a schedule for the leader of sradha bhakti activities, and providing sanctions or punishments that are educational.